Waar lê die diepste punt(e) van verdeling tussen apartheidsteologie en die kritiese stemme daarteen binne die Ned Geref Kerk self? - Coetsee, MH; Conradie, EM (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Where are the deepest points of divergence between apartheid theology and thecritical voices against this theology within the Dutch Reformed Church? This contribution focuses on the relationships between two theological schoolswithin the Dutch Reformed Church (DRC), namely apartheid theology and the earlycritical voices against this theology from within the DRC itself, including BennieKeet, Ben Marais en CF Beyers Naudé. The question that is addressed relates tothe deepest points of divergence in this regard. The significance of this question ishighlighted. Hermeneutical theory (in itself the product of such critical voices) is usedas an instrument to identify a set of seven variables in this regard. The hermeneuticalrole of diverging “doctrinal keys” is emphasised.